Synthesis of surface capped molybdenum sulphide nanoparticles as an antiwear additives for bio-based lubricant oil / Sharul Hafiq Roslan - Sharul Hafiq , Roslan (2017)
Protecting metal surfaces from wear damage is of great concern in internal combustion engine systems. Using suitable additives in lubricant oil is one way of addressing this problem. Molybdenum sulphide additives are widely known for their antiwear and antifriction capabilities, and is fast becoming one of the main ingredients in lubricants. The preparation steps were modified accordingly to obtain nanosized molybdenum sulphide particles, which allows it to be directly blended into the lubricant to form relatively stable particle dispersion. In order to achieve better dispersion and tribological features, the surface of the inorganic material can be protected using various capping agents. In this research, the surface-capped molybdenum sulphide nanoparticles were synthesised, while various alkyl lengths of fatty acids were used as a capping agent. Hexacarbonylmolybdenum was used as a precursor to synthesise molybdenum (II) acetate, which is an organometallic compound intermediate. This compound was then modified with the capping agent to form capped-surface molybdenum sulphide. The properties of surface-capped molybdenum sulphides were determined using Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, X-ray Diffractometry (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX), and Thermal Gravimetric Analyser (TGA). It was then blended into a bio-base oil at concentrations between 0.025-0.125 (w/w) %. The prepared bio-lubricants were then tested using the four-ball tribometer setup, viscometer, and densitometer to determine the friction coefficient (CoF), viscosity, and density, respectively. Scanning Electron Microscopy (SEM) were used to image the wear scars. It is expected that the surface-capped molybdenum sulphide will result in the better antiwear properties and enhanced friction modifying capability.